Behavioral Risk and Sociodemographic Predictors related to HIV infection and other STI's - Piña, Julio (2001)
One thousand thirty-five participants were tested in laboratory in order to detect HIV or other sexually transmitted infection (STI) antibodies between 1999 and 2000. The results showedthat: (a) most of them attended for the first time the Health Information Center; (b) the Elisa test was the most frequently used; (e) the majority were women, and (d) their age range was from 15 to 44 years old. With regard to risk behaviors, the sexual ones were the most frequent;in relation to addictive behaviors, drug consumption by intravenous way and alcohol use were the most frequent ones. Significan! correlation, confirmed by Kolmogrov-Smirnov test, were found among the sociodemographic variables. When analyzing sexual behavior alone and with alcohol consumption, a significant correlation was found in risk behaviors compared to the other variables.